Pathogenscity of vibrio spp. isolated for juvenile p. monodon with red diseases syndrome - Alapid-Tendencia, Eleonor (College of Fisheries and Ocean Sciences, University of the Philippines in the Visayas, 1994)
Bacterial isolation of shrimp (Penaeus monodon) showing symptons of red disease led to the recovery of four Vibrio phenotypes, namely : V. harveyi, V. parahaemolyticus, V. fluvialis, and Vibrio sp. Virulence screening of the two most dominant bacteria - V. harveyi and V. parahaemolyticus - showed V. parahaemolyticus to be more virulent since it has a smallerLT50 value and its causes higher mortality compared to V. harveyi, and induced more severe lesions in the hepatopancreas of injected shrimp. Inoculation of live V. parahaemolyticus cells(106cfu/shrimp) and extracellular crude product in the ventral sinus between the 4th and 5thpleopod produced symptoms of red disease asuch as reddening of the body and lesions likeatrophy of the hepatopancreatic with fibrosis in the intertubular sinus. Melanization, hemocytic infiltration and fibrosis were also observed in the hepatopancreas of pond-reared shrimp affected with red disease, and in the lymphoid organ of these experimentally injected shrimp. Although the results show the role of Vibrio parahaemolyticus in the development ofhepatopancreatic lesions similar to red disease, the exact etiology of red disease syndrome in Penaeusmonodon needs further study.